Demographic Transition and Pension Reforms : Adding Demographics to GIMF - Carton, Benjamin (IMF Working Papers; Working Paper ;, 2020)
The Global Integrated Monetary and Fiscal model (GIMF) is a multi-region, forward-looking, DSGE model developed at the International Monetary Fund for policy analysis and international economic research. This paper documents the incorporation of demographic features into the model. The analysis presented illustrates how these new features enable the model to estimate some of the macroeconomic consequences of changing demographics.